Sociological Analysis of Women's Involvement in Criminal Acts in Tanjungpinang: The Influence of Economy, Family, and Social Environment - Suherry; Mandala, Edward; Usman, Nurbaiti; Prastiyo, Endri Bagus (Journal of Social and Policy Issues, 2024)
This study aims to identify and analyze the factors that cause women to come into conflict with the law in the Tanjungpinang area, focusing on women as perpetrators of criminal acts. The research method utilized involved in-depth interviews with informants who have direct experience related to this issue. The findings indicate that economic factors, social environment, and family conditions are the main drivers of women's involvement in criminal activities. Urgent financial needs often force women to seek quick solutions through illegal avenues, such as fraud and theft. The social environment that permits and normalizes deviant behavior influences individuals' mindsets and actions, thus increasingly driving women to engage in illegal activities. Furthermore, the dynamics within the family, including internal conflicts and lack of emotional support, also contribute to women's decisions to confront the law. In addition to external factors, the psychological and emotional conditions of women, such as poor mental health due to stigma and discrimination, are significant factors that exacerbate their situations. This study emphasizes the importance of social support, appropriate rehabilitation, and educational programs for women involved in criminal behavior. Therefore, this research aims to provide valuable insights for policymakers and the community to develop more effective and inclusive prevention strategies for women in Tanjungpinang.